Perancangan Sistem Informasi Inventory Berbasis Web Pada PT. Gunung Himun Peratama - Muhammad Arfan Bustomi; Alvino Octaviano (CV. Multi Kreasi Media, 2023)
As time goes by, Information Technology (IT) becomes one of the most important medium to improve efective and eveciency in company needs. PT Gunung Himun Peratama is a company that offer cleaning service, whereas offer its not only offer human resources, it offer cleaning tools as well along with the cleaning chemical sent directly from company’s warehouse to the clients. But, in the process if this, I found that the company have something to improve in order to get the system better, which in the process, the company still uses manual proccess that can cause a longer tome tp finish this needs. Organizing stock inventory report that still in manual process is also found another problem in which of the card stock available, sometimes have inaccuracy with the goods. To solve the current problem, I created an informational inventory system with web base which can help the warehouse employees work better with effeciency and more effective